THE TYPOLOGY OF COMPLEX SENTENCES WITH SUBORDINATE CLAUSES (ERGASHGAN QOʻSHMA GAPLAR) IN ENGLISH AND UZBEK - Yoʼldosheva Zarina; Allayev Zafar Mengboyevich (International Journal of Literature and Language Studies, 2026)
This article presents a comprehensive comparative-typological analysis of complex sentences with subordinate clauses (ergashgan qoʻshma gaplar) in English and Uzbek. The article examines the theoretical background of subordination, the formal means of connecting the main clause (bosh gap) and the subordinate clause (ergash gap), and offers a detailed classification of subordinate clause types in both languages, supported by numerous examples. Special attention is given to the typological differences arising from the analytic structure of English and the agglutinative structure of Uzbek, including word order, the position of the subordinate clause, the use of conjunctions versus suffixal markers, and the relationship between finite clauses and non-finite verb forms (participles, gerunds, verbal nouns). The article concludes with practical recommendations for translation and language teaching.